Effects of cold storage on the fitness of Tamarixia radiata, a dominant parasitoid of Asian citrus psyllid Diaphorina citri. (February 2020) - Zhang, Li-He; Lu, Zi-Tong; Guo, Chang-Fei; Shen, Zu-Le; Wang, Zi-Qi; Sang, Wen; Qiu, Bao-Li
Abstract: Low-temperature storage is a valuable method used in the mass rearing of biological control agents to ensure the availability of sufficient individuals (e.g. parasitoids) when required. However, cold storage may decrease the fitness of parasitoids. The purpose of this study was to determine the effect of different cold storage durations on the biological fitness of Tamarixia radiata, a dominant parasitoid of Asian citrus psyllid (ACP), the key vector of the citrus Huanglongbing pathogen. The effects of storage at five temperatures (2, 4, 6, 8 and 10 °C) for periods of 3, 6, 9 or 12 days to a 3-day-old pupal stage of ACP were investigated. Results showed that the eclosion rate of Tamarixia radiata 3-day-old pupae after storage at 10 °C for 6 days was the highest among all treatments. No significant difference of sex ratio was found between the treatment and control groups. The lifetime fecundity after storage at 10 °C for 6 days exceeded 160 which was significantly higher than the other treatments. The size of hindfoot tibia of females and males were 320.28 and 279.63 μm respectively after storage at 10 °C for 6 days. Although the individual size of females was slightly smaller than that of the control group, it was the largest among the treatment groups. Comparing the fitness parameters of the treated T. radiata populations, the vitality of T. radiata after storage for 6 days at 10 °C was at a higher level proving that this was the best combination of temperature and time for low-temperature storage. Highlights: Tamarixia radiata is a dominant parasitoid of D. citri in South China. The adaptability of T. radiata to low temperature was studied for the first time. Effect of cold storage to T. radiata depends on the temperature and storage period. Cold storage at 10 °C for 6 days was the optimal combination T. radiata parasitoids.